Population structure and gene flow of Geoffroy's cat (Leopardus geoffroyi) in the Uruguayan Savanna ecoregion - Bou, Nadia (2021)
Felids are among the species most threatened by habitat fragmentation resulting from land-use change. In the Uruguayan Savanna ecoregion, about 30% of natural habitats have been lost, large felids have been eradicated from most of the region, and the impact of anthropogenic threats over the smaller species that remain is unknown. To develop management strategies, it is important to enhance knowledge about species population structure and landscape connectivity, particularly when land-use change will continue and intensify in the next years. In this study, we evaluate the population structure and gene flow of Geoffroy's cat in the Uruguayan Savanna ecoregion. We generated a matrix of 11 microsatellite loci for 70 individuals. Based on Bayesian approaches we found that within the Uruguayan Savanna, Geoffroy's cat shows high levels of genetic variability and no population structure. However, we observed genetic differences between individuals from the Uruguayan Savanna and those from the contiguous ecoregion, the Argentinian Humid Pampa. Four first-generation migrants from Humid Pampa were identified in the Uruguayan Savanna, suggesting a stronger gene flow in the west-east direction. We detected a past bottleneck followed by a subsequent recovery in Geoffroy's cat populations in both ecoregions. These results lay the groundwork to understand the population dynamics and conservation status of Geoffroy's cat in the Uruguayan Savanna ecoregion, and provide baseline data to establish population monitoring.